2009
DOI: 10.1007/s11664-009-0684-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Modeling of the MWIR HgCdTe Electron Avalanche Photodiode

Abstract: The operation of the mid-wave infrared (MWIR) HgCdTe cylindrical electron injection avalanche photodiode (e-APD) is described. The measured gain and excess noise factor are related to the collection region fill factor. A twodimensional diffusion model calculates the time-dependent response and steady-state pixel point spread function for cylindrical diodes, and predicts bandwidths near 1 GHz for small geometries. A 2 lm diameter spot scan system was developed for point spread function and crosstalk measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The multiplication process is started at low reverse bias. The resultant gain increases exponentially with the reverse bias in our fabricated APD device 49,53 .…”
Section: Avalanche Gainmentioning
confidence: 91%
See 2 more Smart Citations
“…The multiplication process is started at low reverse bias. The resultant gain increases exponentially with the reverse bias in our fabricated APD device 49,53 .…”
Section: Avalanche Gainmentioning
confidence: 91%
“…Finally, it is concluded that electron-injection multiplication process is more favorable from SWIR to LWIR APD for achieving high gain at low reverse bias with low noise. Beck 49,61 , et al have developed MWIR HgCdTe cylindrical p-around-n e-APD with gain~ 1000 and very low gain normalised dark current density (< 0.7 nA/cm 2 ). However, they reported that the planar APD structure provides fill factor~ 100 % and the collection efficiency > 90%, whereas HDVIP diode has advantage to yields low dark current, high quantum efficiency and high operability.…”
Section: Development Of Hgcdte Based Apd Device Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Because this dark current is generated in the multiplication region, it is likely not to be fully gained, and, indeed, noise measurements indicate this. 23 A simplified manner of handling the dark current in the modeling is to use measured dark currents at the bias that achieve the required APD gain. This dark current is then divided by the gain to give a gain normalized dark current.…”
Section: Calculations For Hgcdte Linear Mode Avalanche Photodiode Cammentioning
confidence: 99%
“…High gain with ultra low excess noise factor has been reported in MWIR HgCdTe e-APDs by several groups. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Results on design, fabrication and characterization of e-APD detector arrays using LPE grown p-HgCdTe epilayers are presented in this paper. Consideration of active cum passive modes of operation has been kept in mind in the development of these detector arrays.…”
Section: Introductionmentioning
confidence: 99%